Benin Country Economic Memorandum 2.0 (Vol. 2) : How can Benin’s Demographic Transition Support Economic Growth? - Chapter 2 - World Bank (Washington, DC, 2022)
A small open economy, Benin has seen growth that is above average for the region. The volatility of high growth spells combined with low productivity growth has translated into limited gains in income per capita. Following its transition from low-income country to lower middle income country status in 2020 Benin is at the start of a new growth path. Its challenge is to boost the structural transformation of its economy driven by new growth drivers capable of sustaining an economic acceleration, lifting labor productivity and creating quality jobs for its young labor force, including women. While Benin’s economy has been spared by the worse of the Coronavirus disease 2019 (COVID 19) crisis, the shock has reinforced the need to focus on structural reforms that address long term challenges and ensure that economic recovery is sustainable and inclusive. The key conclusions that underpin this report, following the country economic memorandum (CEM) 2.0 framework suggest that investing further in human capital and closing gender gaps, particularly to accelerate the decline in fertility rates, and integrate women and youth into a higher quality labor market, should be central. Deepening market integration, connecting people and creating agglomeration economies through transport infrastructure and services should catalyze additional opportunities, taking advantage of Benin’s geographical position.